Exploring factors affecting career mobility of female administrative staff at the University of Limpopo South Africa - Matlala, Daniel Kgahlela (My University, 2025)
Most organisations have programmes that facilitate career mobility among the staff to retain valuable employees. Career mobility is often encouraged by the economic push-and-pull factors, as well as the opportunities available in various organisations. As a result, university administrative staff are also affected by the same economic pull-and-push factors prevailing globally. The purpose of this study was to explore the factors influencing the career mobility of female administrative staff at the University of Limpopo, South Africa. The review of the literature for this study showed that numerous South African universities have made significant strides towards gender equity. However, a closer analysis of the data reveals that women are often overrepresented in lower-level positions within these institutions. This research was carried out at the Turfloop Campus of the University of Limpopo, located in Mankweng, Polokwane, in the Capricorn District of Limpopo Province, South Africa. The research used a qualitative approach, using purposive sampling and an interview guide to gather data. Eleven (11) women in administrative roles participated in the study and semi-structured interviews were conducted with the women appointed as administrators at the University of Limpopo. The study revealed significant concerns about the balance of work and home among female administrative staff. The findings indicate a troubling lack of recognition and visibility for female administrative staff within the University. The absence of formal recognition programmes highlights a significant gap in institutional culture, suggesting that efforts to celebrate the achievements of female staff could improve their visibility and encourage a more inclusive environment. In general, the study emphasised the urgent need for the University of Limpopo to implement comprehensive policies that not only promote gender equity, but also actively support the professional growth of female administrative staff. By establishing robust mentoring programmes, improving recognition initiatives, and improving work-life balance provisions, the University can create a more inclusive culture that empowers women to advance in their careers. This transformative approach is essential not only for the individual growth of female staff, but also for the overall success and sustainability of the institution, as diverse leadership is critical to fostering innovation and excellence in higher education.
Thesis (MBA. (Business Administration)) -- University of Limpopo, 2025
Keywords: Career mobility; Female administrative staff; Work-life balance; Career changes; Women employees; Work-life balance; Women employees -- South Africa -- Limpopo; Universities and colleges -- Professional staff